(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The economy of the host region benefits greatly from tourism. It is extremely important in terms of economic growth and job creation. Tourism development has its own impact on the host region’s economic, environmental, socio-cultural, and political development. It creates an opportunity for development of host country and communities. Tourism is a globally prominent socio-economic phenomenon that has grown to turn into one of the greatest sectors with cultural activities. For tourist destinations, it is very important and integral component of life. Every tourist place has its own unique characteristic such as scenic beauty, heritage monument, healthy climate, renowned architecture, biodiversity, religious importance, etc. Tourism has economic, physical and socio-culture impact on the host population of the destination. Now a days tourism industry is one of the global, dynamic and largest developing economic sectors. It helps to initiate infrastructure development, foreign currency inflows, introduction of new educational and management experience, etc. This affects the economy positively and contributes to the social development too. Therefore, the present research paper highlights the major impacts of pilgrimage on physical, socio-cultural and economic aspects at Ozar Pilgrim center.